The Impact of Leadership Styles on Improving Job Performance: A Case Study of the General Organization for Social Insurance in the Riyadh Region (The International Journal for Scientific Research, 2024)
The study aims to know the extent of the impact of leadership styles in improving job performance within the General Organization for Social Insurance in Riyadh, Kingdom of Saudi Arabia, by using the descriptive analytical approach and designing and distributing an electronic questionnaire to a number of leaders and employees in the organization. The sample was selected randomly. The study concluded with a number of results, the most important of which are: different leadership styles are practiced in the General Organization for Social Insurance in Riyadh, but the autocratic style came in first place, followed by the democratic style and the free style, and all of these styles are practiced to an average degree. Also, elements of improving job performance are practiced in the General Organization for Social Insurance in the Kingdom of Saudi Arabia to an average degree. Based on the previous results, the study recommended the following: the need for the General Organization for Social Insurance in the Kingdom of Saudi Arabia to get rid of leadership styles that would limit performance improvement and achieve job creativity. Also, the need to train leaders in the General Organization for Social Insurance in the Kingdom of Saudi Arabia on positive leadership styles
Keywords: Leadership Styles; Job Performance; General Organization for Social Insurance